ANALISIS PENDAPATAN DAN STRATEGI PENGEMBANGAN KOMODITI SIWALAN (Borassus Flabellifer) DI TINJAU DARI SEGI USAHA PEDAGANG NIRA ( Study Kasus Di Desa Kali Anget Kec. Banyuglugur Kab. Situbondo ) - Imam Nawawi; Sumarno Sumarno (Program Studi Agribisnis Fakultas Pertanian, 2015)
The purpose ofthe study is to know the income merchant businesses sap, and commodity prospect siwalan under reviewin terms of merchant businesses sap in the Kalianget village. Hypothesis in this study is the income of trader sap in the Kalianget village favorable and Commodity Development strategies palm in Terms of merchant businesses sap a good to be developed. The method used is descriptive method and survey. Descriptive method is a picture or painting in a systematic, factual, and accurate information on the facts and the relationship between the phenomena investigated. Survey method is to determine the sample that is the field and also write a questionnaire to obtain information needed. Population in this study there are 23 heads of families who do business sales sap, population because there is only 23 traders then all respondens in the sample made in this study that took 23 heads of families who do business in the Kalianget village district Banyuglugur regency of Situbondo. The result showed that the income traders sap in the Kalianget village favorable with the averages income in a month Rp. 403.300,- on weekdays and in the month of ramadhan revenue of Rp 1.854.200,-. Development strategy of business trader sap in the Kalianget village district Banyuglugur regency of Situbondo basad mapping SWOT matrix is in quadrant 1, means the situation is favorable because the strategy to be developed to have good opportunities and strengths, so that the strength that be can take advantage of the opportunities open. Advice is pay attention to the management of research efforts that needs to be improved further sap from the simple to the more modern direction to get better added value.